Dinamika perilaku dan pemberdayaan Kelompok Usaha Bersama (KUB) peternak susu: kasus di Magelang, Jawa Tengah - Wardi, Wardi (Analisis Kebijakan Pertanian, 2024)
Ngablak Village in Magelang District has the potential for goat milk production, however, dairy farmers as members of the Joint Business Group (Kelompok Usaha Bersama/KUB) Surya Abadi experienced obstacles in processing the milk into high-value products. This study aims to analyze the characteristics and behavioral changes of KUB members, evaluate the effectiveness of extension, and formulate recommendations for empowering this dairy farmers’ group through product development of a goat milk kefir with rosella flower extract. The study was conducted in April-June 2023, data collection was carried out through observation and interviews with KUB members. Data analysis used descriptive methods and multiple linear regression. The study showed that the level of empowerment of KUB Surya Abadi was in the high category, with the effectiveness of extension and behavioral change in the effective category. Specifically, age and education have a significant influence, farmers’ experience and the number of livestock have a very significant influence, and counseling intensity is not significant in influencing the level of KUB empowerment. One of the policy implications of this study is that empowerment for KUB needs to be focused on developing innovations and using appropriate extension methods so that these innovations can be accepted and implemented correctly.
Keywords: Karateristik, Motivasi, Pemberdayaan, Peternak